2004
DOI: 10.1097/01.ta.0000105886.89776.82
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Two Scoring Systems to Predict Instability in Fractures of the Distal Radius

Abstract: Both scoring systems were found to underestimate the degree of fracture instability and to have a negative predictive value between 47 and 50% in a prospective series of patients. In fractures predicted to have a low probability of instability in both models, we found a poor correlation between predicted instability and actual instability. Our results demonstrate the limitations of two scoring systems in predicting fracture stability and in making clinical decisions on the basis of their results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…After prospectively reviewing 105 patients, it was found that both scoring systems underestimated the degree of fracture instability. 18 In an attempt to determine signs of early (1 week) and late (6 weeks) instability of conservatively treated extraarticular distal radius fractures in the elderly, an observational study of 71 patients showed that radial shortening and volar tilt greater than 20°were the best predictors of early instability, whereas radial inclination less than 10°, radial shortening, age older than 65 years, and dorsal tilt greater than 20°were predictive of late instability. 19 A prospective, randomized study analyzing 90 patients with displaced intra-articular distal radius fractures with an average of 4-year follow up looked at functional outcomes based on mode of treatment (plaster immobilization, external fixation, plate and screw fixation).…”
Section: Nonoperative Management Closed Treatment With Castingmentioning
confidence: 99%
“…After prospectively reviewing 105 patients, it was found that both scoring systems underestimated the degree of fracture instability. 18 In an attempt to determine signs of early (1 week) and late (6 weeks) instability of conservatively treated extraarticular distal radius fractures in the elderly, an observational study of 71 patients showed that radial shortening and volar tilt greater than 20°were the best predictors of early instability, whereas radial inclination less than 10°, radial shortening, age older than 65 years, and dorsal tilt greater than 20°were predictive of late instability. 19 A prospective, randomized study analyzing 90 patients with displaced intra-articular distal radius fractures with an average of 4-year follow up looked at functional outcomes based on mode of treatment (plaster immobilization, external fixation, plate and screw fixation).…”
Section: Nonoperative Management Closed Treatment With Castingmentioning
confidence: 99%
“…Multiple studies have set out to assess the factors that influence fracture displacement. 2,[4][5][6][7][8][9]12,17 In their 1989 paper, Lafontaine et al studied 112 consecutive cases of displaced distal radius fractures that were managed conservatively. 13 Five criteria were identified that predicted malunion (dorsal comminution, initial dorsal angulation greater than 20 degrees, an intra-articular fracture, an associated ulnar styloid fracture, and patient age greater than 60), and their research suggested that patients with three or more of these factors had an increased risk of loss of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of various classifications demonstrates that there is a need to obtain a single ideal classification that would be very wide-ranging and would provide support for therapeutic and prognostic conduct. 17 More than 20 classification systems for fractures of the distal extremity of the radius have been described. If a classification system has fulfilled all the premises for supplying support, it will still need to present intra and interobserver reproducibility.…”
Section: Discussionmentioning
confidence: 99%